Novel cardioprotective and nephroprotective combination in patients with type 2 diabetes and chronic kidney disease: perspectives of use - Yu. Sh. Khalimov; G. V. Semikova; Yu. A. Shutova (Сахарный диабет)
Chronic kidney disease (CKD) is a common complication of diabetes mellitus. It increases significantly cardiovascular risk and decreases the quality of life. CKD requires treatment, and the treatment paradigm for type 2 diabetes has shifted from a glucose-centric approach towards disease-modifying therapy. Attention is being paid to cardioprotective and nephroprotective effects. In patients with type 2 diabetes and CKD, drugs that affect the renin-angiotensin-aldosterone system, as well as sodium-glucose cotransporter type 2 inhibitors (iSGLT2) are widely used. Despite the proven positive effect of these drugs in preservation of renal functions, the pathogenesis of CKD contains links that have not yet been covered. In particular, the activity of fibrosis processes in the renal parenchyma is increased in patients with CKD due to high expression of mineracorticoid receptors. It may be a potential target for nephroprotective drugs. Thus, mineralocorticoid receptor antagonists (MCRA) may influence the residual risk of CKD progression. In particular, the effectiveness of the non-steroid selective AMCR finerenone has been proven in a number of large clinical studies, which confirmed its nephroprotective potential. In this regard, studies aimed at studying the joint effect of known nephroprotective drugs, as well as their combined effect on cardiovascular risk, are highly needed.This review marks the main mechanisms of the combined action of iSGLT2 and finerenone. Discussion of the results of main clinical studies with combined use of standard nephroprotective therapy, SGLT2 and finerenone is also presented.